Does the posterior approach offer advantages in short-term in trimalleolar ankle fractures? - Holgado-Fernandez, Mario; Galindo-Juárez, German; Muñiz-Zatón, Pedro; Laguna-Bercero, Esther; Menéndez-Solana, Guillermo; Gallardo-Agromayor, Elena; Hernández-Elena, Jesús; Pérez-Núñez , María Isabel (Journal of the Foot & Ankle, 2022)
Objective: The aim of this study was to compare the early (nine months after surgery) synthesis of the posterior malleolus by direct posterior (P) approach versus the percutaneous anteroposterior (AP) screw in trimalleolar ankle fractures to analyze the early clinical status of the patient (eight months) by studying the American Orthopedic Foot And Ankle Society (AOFAS) scale to compare postsurgical clinical recovery between both approaches, the rate of hospital days in both groups, the quality of joint reduction by computed tomography (CT) study and the rate of most frequent complications (fibular tendinopathy and surgical wound). Methods: A retrospective comparative study was performed between 2016-2020, including 94 patients with trimalleolar ankle fracture type 44-A/B/C (27 percutaneous AP surgical treatment and 67 P approach). Both groups were compared by analyzing demographic variables, clinical-functional status, radiological variables, and complications. Statistical analysis was performed using SPSS-20, with a p-value of 0.05 as significance. Results: Demographically, both groups were comparable, not finding significant differences between them. An increase in the days of admission before surgery was observed in the P approach with a mean of 4 (p=0.001). No significant clinical differences were found in the AOFAS scale, with a mean of 85 in both groups. Regarding the radiological result, a better reduction was observed with P approach (good=57, fair=9, poor=0) compared to the AP approach (good=10, fair=7, poor=9) (p=0.001). As for the complications, no significant differences were observed for the surgical wound. However, a higher need for fibular plate removal could be observed with P approach (n=17) (p=0.046). Conclusions: Clinically, both groups observed no significant differences through the AOFAS scale. The posterolateral approach has a higher rate of hospital days before surgery. Radiologically, a better joint reduction is achieved by a direct approach to the posterior fragment. Level of Evidence III; Retrospective Comparative Study.